Development of an IoT-Based PLC Trainer: Bridging the Practical Divide in Industrial Automation Education - Triatmaja, Adhy Kurnia; Budiastuti, Pramudita; Rismarinandyo, Moch Yordan (Universitas Ahmad Dahlan, 2024)
In the dynamic landscape of digitalization, the fusion of Internet of Things (IoT) tech-nology with Programmable Logic Controllers (PLCs) has emerged as a pivotal avenue, promising enriched practical experiences and heightened comprehension. This paper navi-gates through recent studies elucidating the applications of IoT-based PLCs in diverse con-texts, from smart home automation to traffic control and resource management. Notable contributions include remote monitoring systems, smart traffic control, water level moni-toring, and automated greenhouses. Acknowledging persistent challenges in understanding and implementing PLCs, this research introduces an innovative IoT-based PLC Trainer Kit. The kit aims to elevate prac-tical learning by providing hands-on experiences, refining skills, and optimizing applica-tions across various domains. Emphasizing the pivotal role of practical training in PLC education, the study conducts a needs analysis, followed by the design, development, and testing phases of the IoT-based PLC Trainer. The prototype, employing an Omron CPM1A PLC, pneumatic components, sensors, and an intuitive interface, undergoes meticulous testing, affirming its readiness for deployment. The development of the IoT-based PLC Trainer marks a significant achievement, ad-dressing the gap between theoretical knowledge and practical application. Through metic-ulous design, material selection, and testing, the trainer demonstrates optimal functionali-ty and user-friendliness. Anticipating its deployment in educational institutions and in-dustrial setups, the trainer is poised to contribute to the realm of industrial automation, offering a practical understanding of PLC applications within the Internet of Things con-text. This project not only signifies technical expertise but also bridges the gap between theory and practice in the dynamic domain of IoT-driven programmable logic control-lers